Factors Associated With High-Quality Guidelines for the Pharmacologic Management of Chronic Diseases in Primary Care - Arini, Arini; Mustofa, Mustofa (The International Journal of Medical Science and Health Research, 2024)
Background: The literature on the pharmacologic management of chronic diseases in primary care presents a multifaceted view of the challenges and strategies associated with implementing clinical practice guidelines (CPGs). Literature Review: Several articles contribute to this discourse by examining the effectiveness of various implementation strategies. For example, (G C Van Spall et al., 2016) systematically reviews interventions aimed at enhancing physician adherence to CPGs in heart failure management. The authors categorize these interventions by their application level—provider, organization, and systems—highlighting the importance of context in determining their effectiveness. This systematic approach is critical for understanding how to bridge the divide between guidelines and real-world practice. Conclusion: In conclusion, the literature emphasizes the necessity for tailored, context-specific interventions that prioritize both clinical evidence and the unique needs of patients. It is clear that successful implementation of pharmacologic management guidelines in primary care requires a multifaceted approach that includes understanding the complexities of multimorbidity, integrating healthcare professionals such as pharmacists, and actively engaging patients in their care. The collective insights from these articles underscore the importance of adapting guidelines to fit the realities of clinical practice, thereby improving the management of chronic diseases.